(untitled) (Annals of Medical Research, 2021)
Aim: This study aimed to investigate of fetomaternal consequences of placental chorangiosis in preeclamptic and normal pregnant women. Materials and Methods: The study population for this retrospective case-control study was consist of 183 pregnant women (91 pregnant women with preeclampsia and 92 healthy pregnant women). The data on the pregnant women and their infants were obtained from their records; additionally, the placental data were obtained by the histopathological examination of placental samples. Chorangiosis is a vascular hyperplastic process in terminal chorionic villi; that >10 capillary vessels in at least 10 villi of the placenta is called chorangiosis. Results: The case and control groups were similar in terms of their age, gravida, parity, and living and abortion characteristics. The prevalence of chorangiosis, necrosis, and fibrotic villus was high in the placenta of preeclamptic pregnant women; also, their blood values were impaired, and the hospitalization period was longer. Furthermore, the weights and APGAR scores of the infants were low, and the mortality and hospitalization rates were significantly higher. Hence, the presence of preeclampsia and chorangiosis is an important risk factor for the health of both infants and mothers. Conclusion: Although chorangiosis was directly related to negative maternal and fetal outcomes in pregnant women with preeclampsia, more clinical studies with different perspectives are required because chorangiosis was observed in healthy pregnant women as well.